DRE-PCR (Double Repetitive Element-Polymerase Chain Reaction)--nová molekulárnĕ-epidemiologická metoda pri setrení tuberkulózy - Xet-Mull, A M; Kubín, M; Príkazský, V; Harris, E H; Riley, L W (Epidemiologie, mikrobiologie, imunologie, 2001)
In a pilot study Double Repetitive Element-Polymerase Chain Reaction 20 clinical isolates of Mycobacterium tuberculosis from Guatemala and 49 strains from Prague were typed. This technique is based on direct evidence of repetitive elements IS6110 or PGRS and does not require DNA purification, digestion by endonuclease nor Southern blot hybridization. Preliminary examination of Guatemalian strains revealed a striking identity or similarity of DRE-PCR profiles while the Prague strains were characterized by conspicuous polymorphism. The Prague strains were examined in a total number of 13 series of electrophoreograms and subsequently subjected to automated analysis with GelCompar software. The DRE-PCR method is suitable for screening of a major number of clinical isolates of M. tuberculosis in laboratories equipped with a minimum of technical facilities for the PCR method, furthermore it requires facilities for synthesis of the necessary primers and at least basic knowledge of molecular biology.
Keywords: plicní tuberkulóza; Polymerase Chain Reaction; Česká republika; polymerázová řetězová reakce; repetitivní sekvence nukleových kyselin; Bacterial Typing Techniques; lidé; Czech Republic; techniky typizace bakterií; DNA bakterií; DNA, Bacterial; molekulární epidemiologie; DNA Fingerprinting; Guatemala; Humans; Repetitive Sequences, Nucleic Acid; DNA fingerprinting; Molecular Epidemiology; Mycobacterium tuberculosis; Tuberculosis, Pulmonary